2018
DOI: 10.1007/s11606-018-4483-x
|View full text |Cite
|
Sign up to set email alerts
|

Shopping on the Public and Private Health Insurance Marketplaces: Consumer Decision Aids and Plan Presentation

Abstract: The ACA's public health insurance exchanges offered more tools in OEP4 to help consumers select a plan. While private health insurance exchanges presented notable features, the total cost estimates for a standardized consumer varied widely on public versus private exchanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Further research is needed to tailor decision aids to individuals who have low health insurance literacy. Additionally, identification of effective decision aid components (e.g., total cost estimators, quality ratings) can inform future development of decision aids 59 …”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to tailor decision aids to individuals who have low health insurance literacy. Additionally, identification of effective decision aid components (e.g., total cost estimators, quality ratings) can inform future development of decision aids 59 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, health insurance plans can be challenging to understand, especially if the decision-maker has limited financial or health insurance literacy [ 2 , 5 ]. Previous research has shown that the way information is presented in the decision aid can impact consumer choice [ 6 ]. Factors such as the order in which plans are presented, word choice and symbol use, and difficulty in finding information can significantly affect trust in the information and consumer choice [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…VBCs are designed to provide guided support by mimicking a one-on-one interaction with a human resources (HR) representative. Although there has been limited research on health insurance decision aids [ 6 , 9 , 10 ], VBCs are a relatively new product for supporting health insurance choices that combine access to tools, such as cost estimators, and further guidance and recommendations presented through a conversational interface. The effects of this more guided approach to decision-making are still not well understood, and little research has examined how guided systems affect consumer health insurance decision-making when compared with traditional self-directed methods such as websites.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Vardell [38] points out the need for consumers to seek various sources of information (2.8 sources, on average) to fully assess their options. As studies began to highlight the importance of decision aids [39][40][41], these tools became the standard for informed consumer choice when the information was accurate and understood by consumers. Later studies have also shown a greater adoption of some decision support tools by websites for private and public health insurance marketplaces [42,43], a trend that is likely to continue.…”
Section: Introductionmentioning
confidence: 99%